La vinculación positiva de los poderes públicos a los derechos fundamentales - Gavara de Cara, Juan Carlos (Teoría y Realidad Constitucional, 2007)
In the Spanish Constitution, the entailment to fundamental rights operates starting off a double scheme. Article 9.1 CE allows to deduce a negative entailment to the fundamental rights, that is to say, the duty of citizens and public powers of abstaining of any activity that harms the Constitution, which includes tacitly the fundamental rights. Article 53.1 CE settles down specifically the positive entailment to fundamental rights, that affects exclusively the public powers and it consists, first, in a general duty of carrying out its own functions in conformity with the Constitution and, second, in a mandate of developing the effectiveness of the fundamental rights in the sense of establishing its full realization. This article carries out an analysis of the positive entailment, distinguishing and treating the consequences through their subjective or objective implications. The subjective positive entailment has the purpose of determining the consequences for the public powers’ functions that we will distinguish in the three classic powers: legislative, executive and judicial. The objective positive entailment should determine the effects that take place materially to fundamental rights: distinguishing between the defense rights and those of benefit.